Conditioned medium from human cord blood mesenchymal stem cells attenuates age-related immune dysfunctions - Sun, Bo; Meng, Xianhui; Li, Yumin; Li, Yanlong; Liu, Rui; Xiao, Zhongdang (Frontiers in Cell and Developmental Biology, 2023)
Aging is accompanied with progressive deterioration of immune responses and tissue’s function. Using 12-month-old mice as model, we showed that conditioned medium of human cord blood mesenchymal stem cells (CBMSC-CM) significantly reduced the population percentage of CD3-CD335+ NK and CD4+CD25+ regulatory T cells in peripheral blood. The CBMSC-CM administration also increased naïve T cells number and restored the ratio of naïve to memory T cells in CD4+ T cells population. These results indicated that CBMSC-CM improved the immune response efficiency of aged mice. Moreover, we also found CBMSC-CM treatment significantly reduced the number of senescent cells in kidney tissues. Finally, we demonstrated that CBMSC-CM remarkably attenuated hydrogen peroxide triggered T cell response and ameliorated oxidative stress induced cellular senescence. All of these data suggest a prominent anti-aging effect of secretome of CBMSCs.